2021
DOI: 10.1093/ptj/pzab014
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating Treatment-Related Cardiotoxicity in Women Recently Diagnosed With Breast Cancer via a Tailored Therapeutic Exercise Program: Protocol of the ATOPE Trial

Abstract: Objective Therapeutic exercise is already used to ameliorate some of the side effects of cancer treatment. Recent studies examined its preventive potential regarding treatment-related toxicity, which can increase the risk of functional decline and lead to disease recurrence and death. This trial will examine whether the ATOPE (Tailored Therapeutic Exercise and Recovery Strategies) program, performed before treatment (ATOPE-B), can mitigate the onset and extent of cardiotoxicity beyond that ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…Research within breast and colon cancer populations has already demonstrated relevant effects of different exercise interventions on global health status, pain, QoL and fatigue through clinical trials [79][80][81][82][83][84]. Additionally, the results are coincident with other reviews on breast and colon cancer patients [28][29][30][31][32][33], considering that this intervention should be initiated as soon as possible in the early posttreatment period, even from diagnosis, as the literature increasingly supports it [25,85].…”
Section: Discussionmentioning
confidence: 71%
“…Research within breast and colon cancer populations has already demonstrated relevant effects of different exercise interventions on global health status, pain, QoL and fatigue through clinical trials [79][80][81][82][83][84]. Additionally, the results are coincident with other reviews on breast and colon cancer patients [28][29][30][31][32][33], considering that this intervention should be initiated as soon as possible in the early posttreatment period, even from diagnosis, as the literature increasingly supports it [25,85].…”
Section: Discussionmentioning
confidence: 71%
“…The ATOPE trial is an RCT currently recruiting patients with breast cancer and assessing whether tailored therapeutic exercise and recovery strategies can mitigate the onset and extent of cardiotoxicity (Table 3). 117…”
Section: Exercise Programsmentioning
confidence: 99%
“…ATOPE+ was developed by the Biomedical (BIO-277) 'CUIDATE' research group and the Department of Computer Architecture and Technology, CITIC-UGR Research Centre, both from the University of Granada, Spain. The development of ATOPE+ is part of the ATOPE project 28 , registration number NCT03787966 Clini-calTrials.gov, December 2019.…”
Section: Description Of Atope+ and Data Collectionmentioning
confidence: 99%
“…The answers were sent to the server, and the participant received an automatic personalized message about their readiness for either a high-intensity session, a moderate-intensity session, or active recovery. More information about the intervention was published on a previous protocol 28 .…”
Section: Criterion Instrumentmentioning
confidence: 99%